Zmiany miąższości i udziału klas jakości drewna wielkowymiarowego sosnowego w zależności od rodzaju manipulacji dłużyc - Witkowska, Joanna (Leśne Prace Badawcze, 2010)
This paper analyses the volume of large-sized pine wood after it has been subjected to manipulation to meet transport and technological requirements (timber harvest by multifunction machines). Three variants of wood classification are discussed: wood in whole tree-lengths, wood after cutting to logs of 14 metres from the butt end, and wood after bucking into 4-metre logs. Each section was classified and their diameter under bark and length were measured. The results for 400 trees from five stands allowed the impact of manipulation on timber volume to be determined. After cutting a log 14 metres from the butt end, the total volume of wood decreased by 2.65%, and the proportion of classes A and B – by 21.8% and 26.1%, respectively. After bucking into 4-metre logs, the total wood volume decreased by 1.66% and the proportion of classes A and B – by 67.2% and 60.2%.